2018
DOI: 10.3390/f9070420
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil Labile Organic Carbon to a Simulated Hurricane Disturbance in a Tropical Wet Forest

Abstract: Abstract:Hurricanes are an important disturbance in the tropics that can alter forest ecosystem properties and processes. To understand the immediate influence of hurricane disturbance on carbon cycling, we examined soil labile organic carbon (LOC) in a Canopy Trimming Experiment (CTE) located in the Luquillo Experimental Forest of Puerto Rico. We trimmed tree canopy and deposited debris (CTDD) on the forest ground of the treatment plots in December 2014, and collected floor mass samples and 0-10 cm soil sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 59 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…Debris addition temporarily increased tree basal area [49]. Data also suggest that hurricane disturbance can accelerate the cycling of soil labile organic carbon on a short temporal scale of less than two years [82]. In addition, scientists found that both surface-(0-10 cm) and subsoils (50-80 cm) have the potential to significantly increase carbon and nutrient storage a decade after the sudden deposition of disturbance-related organic debris, suggesting Luquillo Experimental Forest soils can serve as sinks of carbon and nutrients derived from disturbance-induced pulses of organic matter [83].…”
Section: Canopy Trimming Experiments (2002-today)mentioning
confidence: 89%
“…Debris addition temporarily increased tree basal area [49]. Data also suggest that hurricane disturbance can accelerate the cycling of soil labile organic carbon on a short temporal scale of less than two years [82]. In addition, scientists found that both surface-(0-10 cm) and subsoils (50-80 cm) have the potential to significantly increase carbon and nutrient storage a decade after the sudden deposition of disturbance-related organic debris, suggesting Luquillo Experimental Forest soils can serve as sinks of carbon and nutrients derived from disturbance-induced pulses of organic matter [83].…”
Section: Canopy Trimming Experiments (2002-today)mentioning
confidence: 89%
“…Tropical forest hurricanes rapidly deposit large amounts of leaf litter and woody debris from the canopy to the forest floor [4] , [5], [6], [7], which then results in short to long-term changes to the forest structure and forest ecological processes [4] associated with the rapid increase in the C and N nutrients [8], [9], [10], [11]. This increase in nutrients and enhancement of the ecological processes are thought to influence the soil microbial communities [12], [13], yet, very little is known about how hurricanes influence these communities.…”
Section: Discussionmentioning
confidence: 99%
“…In field experiments in which canopy material was cut and dropped to the forest floor to simulate the effects of a hurricane, nutrient pulses of more labile forms of C, N and phosphorus derived from the younger leaf litter from the canopy were processed in the first year post deposition of material [4][6] [9] [10] [16] [17]. Following this, Liu et al ( [10]) showed the initial pulse of labile organic C and nutrient turnover rate in the forest soil lasted from about the first week to about 2 years. They also showed there was an elevation of the soil microbial biomass that lasted from week 1 until at least 120 weeks after deposition of the canopy material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations